Exploration of phase diagram, structural and dynamic behavior of [HMG][FSI] mixtures with NaFSI across an extended composition range. Issue 27 (30th June 2022) - Biernacka, Karolina; Makhlooghiazad, Faezeh; Popov, Ivan; Zhu, Haijin; Chotard, Jean-Noël; O'Dell, Luke A.; Sokolov, Alexei P.; Pringle, Jennifer M.; Forsyth, Maria
Abstract : In this study we present a detailed exploration of the complex structural and dynamic behavior of [HMG][FSI] mixtures with the sodium salt NaFSI across the whole composition range from 0 to 100 mol%. Abstract : Hexamethylguanidinium bis(fluorosulfonyl)imide ([HMG][FSI]) has recently been shown to be a promising solid state organic ionic plastic crystal with potential application in advanced alkali metal batteries. This study provides a detailed exploration of the structural and dynamic behavior of [HMG][FSI] mixtures with the sodium salt NaFSI across the whole composition range from 0 to 100 mol%. All mixtures are solids at room temperature. A combination of differential scanning calorimetry (DSC), synchrotron X-ray diffraction (SXRD) and multinuclear solid state NMR spectroscopy is employed to identify a partial phase diagram. The 25 mol% NaFSI/75 mol% [HMG][FSI] composition presents as the eutectic composition with the eutectic transition temperature at 44 °C. Both DSC and SXRD strongly support the formation of a new compound near 50 mol% NaFSI. Interestingly, the 53 mol% NaFSI [HMG][FSI] composition was consistently found to display features of a pure compound whereas the 50 mol% materials always showed a second phase. Many of the compositions examined showed unusual metastable behaviour. Moreover, the ion dynamics as determined by NMR, indicate that the Na + and FSI − anions are signifcantly more mobile than the HMG cation in the liquid state (including the metastable state) for these materials.